Sufism and Religious Moderation in Counter Radicalism - Bindaniji, Muhamad; Fuadi, Moh Ashif (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2022)
The discourse of religious moderation is still an interesting discussion, especially among academics. Some circles greeted religious moderation with a positive and negative responses. This study aims to formulate the concept of religious moderation based on other approaches or not the same as in general, such as Sufism, renewal of thought, secularization, and local wisdom. Through the library research method strengthened by interviews, observations, and sources of written documents, whether articles, books, or online news, this research concluded that Sufism could prevent radical behavior because it is precisely radical inward, in contrast to extremists who are radically patterned outwards. Second, the enlightenment of religious thought, mainly carried out by the Nahdlatul Ulama circle, plays a strategic position in stemming radical thinking. Third, the accusations of religious moderation that are considered projects of religious secularization are very unfounded and excessive because they do not fit the context of space and time. Fourth, one of the moderate indicators is to appreciate local wisdom, not that it means that you must like or follow the existing traditions and culture.